Pengaruh Literasi Keuangan Syariah, Teknologi Finansial Berbasis E-Wallet, dan Gaya Hidup Halal, Terhadap perilaku konsumsi Islami pada Generasi Z di Kota Bengkulu - Nanda Puspitasari; Herlina Yustati; Khozin Zaki (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to determine the effect of Islamic financial literacy, e-wallet-based financial technology, and halal lifestyle on Islamic consumption behavior among Generation Z in Bengkulu City. The background of this study is based on the many recent phenomena related to consumption behavior, including impulsive shopping, where some individuals, especially Generation Z, tend to buy goods excessively through online shopping due to the temptation of discounts or flash sales even though the goods are not necessarily needed. The data obtained from this study comes from a questionnaire that has been distributed to Generation Z in Bengkulu City who have used E-wallet. The sample was taken using a purposive sampling technique. This study uses a quantitative method using d3escriptive statistical analysis, validity tests, reliability tests, classical assumption tests, linearity tests, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that the variables of Islamic financial literacy and halal lifestyle have a positive and significant relationship with Islamic consumption behavior among Generation Z in Bengkulu City, while E-wallet-based Financial Technology does not have a significant influence on Islamic consumption behavior among Generation Z in Bengkulu City